The impact of improving capital stock on the utilization of local health services: Preliminary findings on the evaluation of the health facilities enhancement program - Oscar F. Picazo; Ida Marie Pantig; Danica Aisa Ortiz; Melanie Aldeon; Nina Ashley Dela Cruz; Juan Alfonso Tanghal (Philippine Institute for Development Studies (PIDS), 2016)
This impact evaluation of the Health Facilities Enhancement Program (HFEP) of the Department of Health provides a preliminary analysis on its effects, particularly on the utilization of local health services, due to the improvement in capital stock. Furthermore, the evaluation attempts to present certain problems and issues encountered in the implementation of the program. The first part of this paper provides a general overview of what an impact evaluation is and gives the sampling frame of the study. Site visits were conducted in 107 hospitals/infirmaries and 159 rural health units/city health offices. These include HFEP-recipient and a few non-HFEP recipient facilities. An overview of facilities that received HFEP grants is then provided, as well as the completion and functionality of HFEP infrastructure projects in visited facilities.In the conduct of the impact evaluation, health service utilization through number of birth deliveries, outpatient consultations, and inpatients was compared in both HFEP and non-HFEP facilities. The aim is to identify trends and patterns in utilization, if there is an increase. Subsequently, bottlenecks in the evaluation were also revealed, particularly in comparing the volume of services before, during, and after HFEP. In connection to this, some analytical challenges concerning confounding factors and some proposed analytical approaches in undertaking an impact evaluation of capital investments are also given. The final part of this paper provides a conclusion on the impact of HFEP in health utilization, and some proposed areas for further study and research.
Keywords: 330; health facilities; HFEP; health infrastructure; medical equipment